The Change In Seismic Intensity Effects On The Stability Of The Dam Duwaisat (Journal of Hama University, 2026)
In this research static and dynamic analysis study of AL-Duwaisat Dam assess the safety of this dam In cases various downloads then study the effect of seismic intensity this is when it likely to be exposed to earthquakes high seismic intensity we studied the stability of both sides In cases various downloads spencer s way using program Geo-Studio where ve used the subprogram Slope /w to study balance and stability from the study of seismic intensity changes this affected the stability and Safety Factor of dam in addition to making a comparison between safety factors And partial Safety factors in the case if static analysis